A novel hybrid approach for the optimization of double‐diode model parameters of solar cell. (1st June 2022) - Kanimozhi, G.; Kumar, Harish; Satyanarayana, N.
Summary: In the present work, the intrinsic parametric quantities of the solar cell are attempted to determine by the proposed Lambert W‐based double‐diode model as a novel hybrid approach. The proposed hybrid approach is tested with three metaheuristic algorithms. The solar cell double‐diode model parameters are optimized by three different metaheuristic methods viz., Ant Lion Optimizer, firefly algorithm, and sine‐cosine algorithm. The conventional solar cell model equation is non‐linear in nature. An equivalent equation in terms of the Lambert W function is used for the optimization process. The performance of these three methods is compared by their respective root‐mean‐squared‐error value, convergence process, and optimization time. The proposed hybrid approach method of optimization has yielded good RMSE values in the order of 10 − 3 for the three tested metaheuristic algorithms. It is found that among the three proposed methods, Lambert W‐based sine‐cosine algorithm outperforms the other two methods and is considered to be a promising technique for investigating photovoltaic performance.